2021
DOI: 10.18276/cej.2021.3-05
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modified High Intensity Interval Training on Fat Loss

Abstract: Exercise has multiple health benefits and is a critical component in managing overweight and obesity. High Intensity Interval Training (HIIT) involves brief high-intensity anaerobic exercise followed by rest or very low intensity exercise. 24 men and women (age 18-60 years) volunteered to participate in a 6 weeks of modified HIIT exercises program where whole body functional training exercises was provided. Their body weight, body mass index, waist to hip ratio and skin fold fat were measured at the beginning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…There was such substantial individual variability that it was possible to distinguish Rs and NRs based on BFP. Study conducted by Dominic and Kishore 50 showed the effectiveness of HIIT on BF reduction, which was confirmed in a meta-analysis by Khodadadi et al 51 . With joint improvement in body composition, increased CRF 52 and motor fitness 53 are observed.…”
Section: Discussionmentioning
confidence: 69%
“…There was such substantial individual variability that it was possible to distinguish Rs and NRs based on BFP. Study conducted by Dominic and Kishore 50 showed the effectiveness of HIIT on BF reduction, which was confirmed in a meta-analysis by Khodadadi et al 51 . With joint improvement in body composition, increased CRF 52 and motor fitness 53 are observed.…”
Section: Discussionmentioning
confidence: 69%
“…The benefits of HIIT are usually observed in many health-related fitness outcomes from each of its component: body composition, muscular strength and endurance, and cardiorespiratory fitness [27] are related to outcomes that are often achieved in a few areas; however, there is a lack of deeper insight into individual responses, which may be different due to physiological processes [28][29][30].…”
Section: Discussionmentioning
confidence: 99%